Carcass and Meat Quality in Ruminants - Ripoll, Guillermo; Panea, Begoña (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dear Colleagues, Ruminant production systems are very important in many areas of the world and a key aspect of the economy and culture. Food quality is a complex term that includes, in addition to safety, such intrinsic characteristics as appearance, color, texture, and flavor, which are modified by both pre- and post-mortem factors. For this Special Issue, we included studies on any of these factors or preservation methods for improving the quality and shelf-life of meat. We also collected manuscripts on carcass development, quality, and valorization. We are interested in applied research and the interaction between pre- and post-mortem factors, e.g., nutrition and preservation methods for improving the quality and conservation of a carcass and meat, and methods for assessing carcass quality (ultrasound, image analysis, etc.). However, manuscripts related to the extrinsic characteristics (origin, quality labels, price, etc.) of a carcass or meat do not fall into the scope of this Special Issue.